Comparision Between Adaptive Digital Base Band Predistortion Technique And Other Techniques For Power Amplifier - Mohammady, Somayeh (2008)

(untitled)
The purpose of the Power Amplifier is to boost the radio signal to a sufficient power level for transmission through the air interface from the transmitter to the receiver. It involves solving several contradicting requirements, which are such as linearity and efficiency. Unfortunately, these requirements tend to be mutually exclusive, so that any improvement in linearity is usually achieved at the expense of efficiency, and vice versa. A lot of studies and reviews on different classes of power amplifiers, their characteristics and distortion parameters have been done. This includes a study on different technique to improve the linearity of power amplifier, where each technique was reviewed to determine its suitability for the proposed applications. In this research, the adaptive digital predistortion technique was been studied and compare with other techniques. The predistortion circuit inversely models the amplifier's gain and phase characteristics and, when combined with the amplifier, produces an overall system that is more linear and reduces the amplifier's distortion. In essence, "inverse distortion" is introduced into the input of the amplifier, thereby canceling any non-linearity that the amplifier might have. This inverse distortion is the data stored in look-up table that is being multiplied into the input signal and then the customized input signal is ready to pass through power amplifier. By analyzing the output signal and the desired signal, the adaptation algorithm will update this data until finding the optimum values. In this thesis, Saleh model was used as a model of power amplifier and been compared with the others results of the model for verification. The Saleh model was used for the adaptive digital predistortion studies to linearize the power amplifier. Simulation and results of this amplifier demonstrate between 15dB to 20dB improvements in output spectrum that means there is 60% to 65% improvement in linearization, maximum 20% improvement in Gain of Power Amplifier, 15% improvement in Power efficiency, and noticeable cancellation in constellations changes.